Long memory in German energy price indices - Carlos Pestana Barros; Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2012)
This study examines the long-memory properties of German energy price indices (specifically, import and export prices, as well as producer and consumer prices) for hard coal, lignite, mineral oil and natural gas adopting a fractional integration modelling framework. The analysis is undertaken using monthly data from January 2000 to August 2011. The results suggest nonstationary long memory in the series (with orders of integration equal to or higher than 1) when breaks are not allowed for. However, endogenous break tests indicate a single break in all series except for producer prices for lignite for which two breaks are detected. When such breaks are taken into account, and with autocorrelated disturbances, evidence of mean reversion is found in practically all cases.
Keywords: C32; E30; 330; energy prices; Germany; fractional integration; persistence; breaks and outliers; Energiepreis; Zeitreihenanalyse; Schätzung; Deutschland